Method for manufacturing laminate of iron-based amorphous alloy
Patent Information
- Application Number
- JP2024543830
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-02
- Filing Date
- 2023-07-04
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-07-04
AI Technical Summary
【0025】 本発明の鉄基非晶質合金の積層体の製造方法によれば、良好な軟磁気特性を確保しつつ打抜き加工を容易に行うことができるので、例えば、EV駆動用BLDCモータ向けコア材の製造に好適に使用することができる。
Smart Images

Figure 0007645026000004 
Figure 0007645026000005 
Figure 0007645026000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an iron-based amorphous alloy laminate, and more particularly to a method for producing an iron-based amorphous alloy laminate that can be suitably used for laminated cores for motors, generators, etc. [Background technology]
[0002] In recent years, iron-based amorphous alloy materials, whose main raw materials are iron (Fe), boron (B), and silicon (Si), have become known for use in various passive elements and transformers, such as inductors and reactors used as electronic components. Fe-Si-B-based rapidly solidified alloy ribbons with a thickness of about 17 μm to 22 μm, produced by the molten metal rapid solidification method using such soft magnetic materials, are used as winding cores for large transformers for power transmission and rectifier inductors, and demand for them as an alternative to conventional silicon steel sheets (Fe-Si) is increasing year by year.
[0003] In addition, because iron-based amorphous alloys have lower iron loss than silicon steel sheets, their application to the rotor and stator cores of BLDC (brushless direct current) motors is being considered to improve motor efficiency. In particular, when applied to high-speed BLDC motors that exceed 10,000 rpm, the operating range of soft magnetic materials is in the high-frequency band of 1 kHz or more, and it has been confirmed that the improvement in efficiency is more pronounced in motors in the hundreds of watts class. For example, it is expected that these materials will be used in white goods such as air conditioner compressors and rechargeable vacuum cleaners, as well as auxiliary motors for electrical equipment.
[0004] Drive motors for EVs, which require even higher efficiency than motors for white goods, are also shifting to high-speed BLDC motors with rotation speeds of 10,000 rpm or more (for example, around 20,000 rpm) due to market demands for miniaturization, high torque, and high efficiency.For this reason, iron-based silicon boron amorphous alloys are being considered as soft magnetic materials that are expected to operate in the 1 to 2 kHz range when used as motor cores.
[0005] Iron-based silicon boron-based amorphous alloys can reduce core loss to about 1 / 10 compared to silicon steel sheets, and have high magnetic permeability and a relatively high Bs (saturation magnetic flux density), so they have been attracting attention in recent years as next-generation high-performance soft magnetic materials. However, the thickness of iron-based silicon boron-based amorphous alloys is generally about 17 to 25 μm, which is significantly thinner than the thickness of silicon steel sheets, which is about 250 to 350 μm, making it difficult to punch them to manufacture laminated cores, etc. Therefore, the challenge is to increase the amount of iron-based silicon boron-based amorphous alloys produced while maintaining good properties.
[0006] For example, Non-Patent Document 1 discloses that the addition of phosphorus (P) reduces the quenching solidification rate and produces an iron-based amorphous alloy ribbon with a thickness of 50 μm or more. However, phosphorus-added alloys not only cause a decrease in Bs due to the addition of phosphorus, but also have the risk of causing significant contamination inside and outside the molten metal quenching device due to the volatilization of the phosphorus component during alloy melting, and are also flammable, so there are still few examples of their application in the industrial field.
[0007] Patent Documents 1-3 disclose a method for producing an amorphous alloy ribbon having a thickness (e.g., about 50 μm) that allows punching by a multiple slit method in which molten alloy is poured from multiple slit nozzles onto a rotating cooling roll. However, even with such a technique, there is a limit to how much the thickness can be increased, making it difficult to use the ribbon as a soft magnetic material for laminated cores to replace silicon steel sheets.
[0008] Patent Document 4 discloses a method for manufacturing a metal ribbon using a multi-hole nozzle to prevent the thickness of the metal ribbon from becoming non-uniform when a wide quenched ribbon is produced. The invention of Patent Document 4 is characterized by the shape of the nozzle opening, but there is a problem that the nozzle processing cost rises due to the difficulty of processing, making it difficult to use on a mass production level.
[0009] Patent Document 5 discloses a method for producing an iron-based silicon boron-based amorphous alloy using a discharge nozzle with a staggered multi-orifice to produce a thick plate. However, compared to silicon steel plate, there is still room for improvement in terms of ensuring a sufficient thickness.
[0010] Since it has been conventionally difficult to increase the thickness of an amorphous alloy ribbon itself as described above, Patent Document 6 discloses a method for manufacturing a laminate in which a plurality of soft magnetic alloy ribbons are stacked to increase the thickness. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 5-329587 [Patent Document 2] Japanese Patent Application Publication No. 7-113151 [Patent Document 3] Japanese Patent Application Publication No. 8-124731 [Patent Document 4] Japanese Patent Application Publication No. 63-220950 [Patent Document 5] JP 2018-153828 A [Patent Document 6] Patent Publication No. 2021-154732 [Non-patent literature]
[0012] [Non-Patent Document 1] Creation of new bulk metallic glass / amorphous thick plates with high saturation magnetic flux density (Tohoku University, Metallic Glass Research Center) Akihiro Makino, Ken Kubota, Tono Chuntao Summary of the Invention [Problem to be solved by the invention]
[0013] The method for manufacturing a laminate of soft magnetic alloy ribbons disclosed in Patent Document 6 involves applying a thermosetting resin to at least one of a plurality of soft magnetic alloy ribbons, bonding them together, and then heating and adhering them at a predetermined temperature to form a laminate, which is then wound into a coil. When manufacturing a laminated core from the laminate obtained by this manufacturing method, the laminate is unwound from the wound state, punched out into a plurality of core pieces by punching, and then each core piece is crimped and laminated.
[0014] In the manufacturing method of a laminate of soft magnetic alloy ribbons disclosed in Patent Document 6, the soft magnetic alloy ribbon may be either an amorphous alloy ribbon or a nanocrystalline alloy ribbon obtained by subjecting an amorphous alloy ribbon to heat treatment. However, the heat treatment conditions have a large effect on the magnetic permeability of the soft magnetic alloy ribbon, and therefore there is room for further study in terms of ensuring good soft magnetic properties.
[0015] In addition, in the manufacturing method of the laminate of the soft magnetic alloy ribbons disclosed in Patent Document 6, since the manufactured laminate is wound into a coil, misalignment is likely to occur between the multiple soft magnetic alloy ribbons constituting the laminate, and there is a risk that some of the soft magnetic alloy ribbons may peel off. Therefore, the characteristics of the laminated core manufactured by unwinding the laminate are likely to vary, and there is a risk that sufficient quality cannot be obtained.
[0016] To achieve high efficiency in high-speed motors such as drive motors for next-generation EVs, which are designed to operate at high speeds of 10,000 rpm to 20,000 rpm, low iron loss and high magnetic permeability are required for silicon steel sheets, which are the existing core material, and specifically, soft magnetic properties of Bs ≥ 1.5 T, magnetic permeability ≥ 3000, and iron loss ≤ 30 W / kg (at Bm: 1.0 T, 1 kHz) are required. Furthermore, there is a strong demand, mainly from the automotive industry, for an iron-based amorphous alloy as a core material for BLDC motors for EV drives, that has such good soft magnetic properties while also having a thickness that allows the manufacture of laminated cores by punching with the same level of efficiency as silicon steel sheets.
[0017] SUMMARY OF THE PRESENT DISCLOSURE An object of the present invention is to provide a method for producing a laminate of an iron-based amorphous alloy that can be easily punched while maintaining good soft magnetic properties. [Means for solving the problem]
[0018] The object of the present invention is to provide a method for producing a laminate by laminating a plurality of iron-based amorphous alloy ribbons, 100-x-y-z S x (B 1-m C m ) y P z (T is at least one element selected from the group consisting of Fe, Co, and Ni, and is a transition metal element necessarily including Fe), the composition ratios x, y, z, and m satisfy 2.5≦x≦7.0 atomic %, 13.0≦y≦16.0 atomic %, 0.0≦z≦2.0 atomic %, and 0.0≦m≦0.3, respectively, the thickness of the iron-based amorphous alloy ribbons being 30 μm or more and 60 μm or less, and the method for producing a laminate of the iron-based amorphous alloy ribbons includes the steps of: a pretreatment step of heat-treating a plurality of the iron-based amorphous alloy ribbons at a temperature of 200° C. or more and lower than a crystallization temperature; a coating step of coating a thermosetting resin on at least one of the iron-based amorphous alloy ribbons after the heat treatment to form an adhesive layer; and a thermocompression bonding step of thermocompression-bonding the plurality of the iron-based amorphous alloy ribbons via the adhesive layer to form a laminate.
[0019] In the pretreatment step, the heat treatment is preferably performed for a heat treatment time of 0.01 seconds or more and 2 hours or less.
[0020] The pretreatment step preferably comprises stacking a plurality of the iron-based amorphous alloy ribbons in close contact with each other and subjecting them to a heat treatment, and the coating step preferably comprises separating the stacked iron-based amorphous alloy ribbons to form the adhesive layer.
[0021] It is preferable to further include a punching step of conveying the laminate of the iron-based amorphous alloy ribbons obtained by the thermocompression bonding step to a punching press without winding it up, and punching it into a predetermined shape by the punching press to form a punched piece.
[0022] The thermocompression bonding step is preferably performed by holding the temperature at 120° C. or higher and lower than 400° C. for 1 second or higher and shorter than 60 seconds, and the thickness of the laminate of the iron-based amorphous alloy ribbons is preferably 80 μm or higher and 400 μm or lower.
[0023] In the thermocompression bonding step, the pressure when thermocompression bonding is performed by holding at a temperature of 120° C. or more and less than 400° C. for 1 second or more and less than 60 seconds is preferably 30 N or more and 1 kN or less per square centimeter, more preferably 100 N or more and 700 N or less, and even more preferably 100 N or more and less than 400 N. This makes it possible to easily ensure good adhesion between the laminates without peeling off when punching the laminates made of the iron-based amorphous alloy ribbon.
[0024] The iron-based amorphous alloy ribbon that has been subjected to the pretreatment step preferably has a Bs of 1.5 T or more, a magnetic permeability of 3000 or more, an iron loss of Bm=1.0 T, and a frequency of 1 kHz of 30 W / kg or less. Effect of the Invention
[0025] According to the method for producing a laminate of an iron-based amorphous alloy of the present invention, punching can be easily performed while maintaining good soft magnetic properties, and therefore the laminate can be suitably used, for example, for producing a core material for a BLDC motor for driving an EV. [Brief description of the drawings]
[0026] [Figure 1] 2 is a flow chart for explaining a method for manufacturing a laminate of an iron-based amorphous alloy according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic process diagram showing a method for producing a laminate of an iron-based amorphous alloy according to one embodiment of the present invention. [Diagram 3] FIG. 4 is a schematic process diagram showing a method for producing a laminate of an iron-based amorphous alloy according to another embodiment of the present invention. [Figure 4] FIG. 4 is a schematic process diagram showing a method for producing a laminate of an iron-based amorphous alloy according to still another embodiment of the present invention.
Best Mode for Carrying Out the Invention
[0027] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. FIG. 1 is a flowchart for explaining a method of manufacturing a laminate of an iron-based amorphous alloy according to an embodiment of the present invention. As shown in FIG. 1, the method of manufacturing a laminate of an iron-based amorphous alloy according to the present embodiment includes a pretreatment step S1 of heat-treating a plurality of iron-based amorphous alloy ribbons, a coating step S2 of forming an adhesive layer on the iron-based amorphous alloy ribbons after heat treatment, a thermocompression bonding step S3 of bonding and thermocompression bonding a plurality of iron-based amorphous alloy ribbons through the adhesive layer, and a punching step S4 of punching the laminate obtained by thermocompression bonding into a predetermined shape to form punched pieces. Hereinafter, each of steps S1 to S4 will be described with reference to the schematic process diagram shown in FIG. 2.
[0028] <S1: Pretreatment Step> As disclosed in Patent Document 5 above, the iron-based amorphous alloy ribbon is preferably formed into a ribbon shape by a single-roll melt rapid solidification method in which a molten alloy is rapidly cooled and solidified by contact with a cooling roll. As shown in FIG. 2, in the pretreatment step S1, a plurality (three in this embodiment) of iron-based amorphous alloy ribbons 1 are unwound from the state of being wound around the feed roll 10 and conveyed to the pretreatment constant temperature bath 20, and heat treatment is performed in the pretreatment constant temperature bath 20.
[0029] The iron-based amorphous alloy ribbon 1 has a composition formula of T 100-x-y-z Si x (B 1-m C m ) y P z (T is at least one element selected from the group consisting of Fe, Co, and Ni, and is a transition metal element that necessarily contains Fe), and the composition ratios x, y, z, and m satisfy 2.5 ≦ x ≦ 7.0 atomic%, 13.0 ≦ y ≦ 16.0 atomic%, 0.0 ≦ z ≦ 2.0 atomic%, and 0.0 ≦ m ≦ 0.3, respectively.
[0030] If the iron-based amorphous alloy ribbon 1 is too thin, the number of layers required to form a laminate increases, which may lead to an increase in manufacturing costs, while if the iron-based amorphous alloy ribbon 1 is too thick, manufacturing becomes difficult, so the thickness is set to 30 μm or more and 60 μm or less. The width of the iron-based amorphous alloy ribbon 1 is not particularly limited, but is, for example, 10 to 200 mm when it is used as a motor core.
[0031] The heat treatment temperature in the pretreatment step S1 is set to a temperature equal to or lower than the crystallization temperature of the iron-based amorphous alloy, since if the temperature is raised to a temperature at which clusters, which are precursors of the crystalline phase, or nano-order crystals resulting from the crystallization of the clusters, crystallize in the iron-based amorphous alloy, as in the conventional method, the magnetic permeability decreases, making it difficult to obtain the desired soft magnetic properties. The crystallization temperature is the temperature (inflection point) at which heat generation due to crystallization of the iron-based amorphous alloy starts, and can be measured by a differential scanning calorimeter (DSC) or a differential thermal analyzer (DTA). The specific crystallization temperature varies depending on the alloy composition, etc., but is, for example, 350 to 500°C.
[0032] On the other hand, if the heat treatment temperature in the pretreatment step S1 is too low, the soft magnetic properties of the iron-based amorphous alloy ribbon 1 are not improved, so the heat treatment temperature is set to 200° C. or higher. The heat treatment temperature in the pretreatment step S1 is preferably 240 to 280° C. In this way, by setting the heat treatment temperature in the pretreatment step S1 lower than the conventional one, the iron-based amorphous alloy ribbon 1 is cooled in a short time, and the next coating step S2 can be started early, so that the transport distance and transport speed of the iron-based amorphous alloy ribbon 1 until the next step can be shortened and the manufacturing efficiency can be improved. When the thickness of the iron-based amorphous alloy ribbon 1 is relatively large (30 μm or more and 60 μm or less), the heat treatment temperature in the pretreatment step S1 is important in obtaining good soft magnetic properties.
[0033] The heat treatment in the pretreatment step S1 may be performed instantaneously. By shortening the heat treatment time, the pretreatment constant temperature bath 20 can be downsized. Specifically, the heat treatment time is preferably 0.01 seconds or more. There is no particular upper limit for the heat treatment time, but if it becomes too long, the manufacturing efficiency will be significantly reduced. Therefore, for example, it is 2 hours or less.
[0034] The pretreatment step S1 is preferably performed in a state where a plurality of iron-based amorphous alloy ribbons 1 are overlapped and adhered to each other by the pressure rollers 21 and 22. Thereby, the heat treatment of each iron-based amorphous alloy ribbon 1 can be performed efficiently in a space-saving manner.
[0035] The iron-based amorphous alloy ribbon 2 after the heat treatment by the pretreatment step S1 can easily achieve soft magnetic properties with Bs of 1.4 T or more, a magnetic permeability of 3000 or more, and an iron loss of 30 W / kg or less at Bm = 1.0 T and a frequency of 1 kHz, which are applicable to a laminated core for a small and high-efficiency EV drive BLDC motor.
[0036] <S2: Coating Step> The iron-based amorphous alloy ribbons 2 after the heat treatment are discharged from the pretreatment constant temperature bath 20 in a state where a plurality of them are overlapped. In the coating step S2, after separating each iron-based amorphous alloy ribbon 2, an adhesive is applied to one or both of the respective joint surfaces when the plurality of iron-based amorphous alloy ribbons 2 are laminated again by the coating device 31. The coating device 31 of the present embodiment is a spray type, but a roll coater, a curtain coater, a dispenser, etc. may be used. The adhesive is made of a thermosetting resin, and an epoxy resin is used in the present embodiment, but a polyester resin, a polyimide resin, a polyurethane resin, etc. may also be used. The application of the adhesive to the iron-based amorphous alloy ribbon 2 after the heat treatment is preferably performed uniformly over the entire joint surface. The film thickness of the adhesive is, for example, 0.1 μm to 20 μm.
[0037] The adhesive applied to the iron-based amorphous alloy strip 2 after heat treatment is dried by a drying device 32 such as a heater during the process of being conveyed toward a thermocompression constant-temperature bath 40 for performing the thermocompression process S3 in the next step. Thus, an adhesive layer 3 is formed on the bonding surface of the iron-based amorphous alloy strip 2.
[0038] <S3: Thermocompression Process> In the thermocompression process S3, each iron-based amorphous alloy strip 2 after heat treatment is bonded together through the adhesive layer 3 by pressure rolls 41 and 42 and thermocompressed in the thermocompression constant-temperature bath 40 to form a laminate 4 of the iron-based amorphous alloy strips 2. If the heating temperature of the laminate 4 in the thermocompression process S3 is too low, sufficient adhesive force cannot be exhibited due to insufficient curing of the adhesive layer 3. On the other hand, if it is too high, there is a risk of a decrease in the adhesive strength between the iron-based amorphous alloy strips 2 after the curing of the adhesive layer 3, so in the punching process S4 of the next step, delamination between the iron-based amorphous alloy strips 2 constituting the laminate 4 is likely to occur. Therefore, in order to ensure good adhesion between the iron-based amorphous alloy strips 2, it is preferably set to a temperature of 120°C or higher and less than 400°C in the thermocompression constant-temperature bath 40, and more preferably 150°C or higher and less than 350°C. The heating time by holding the laminate 4 in the thermocompression constant-temperature bath 40 is preferably 1 second or more and less than 2 hours, more preferably 5 seconds or more and less than 1 hour, and even more preferably 7 seconds or more and less than 30 minutes.
[0039] The thermocompression pressure in the thermocompression process S3 is preferably 30 N or more and 1 kN or less per square centimeter. If the thermocompression pressure is lower than 30 N, sufficient adhesion between the bonded iron-based amorphous alloy strips 2 cannot be ensured. On the other hand, if the thermocompression pressure exceeds 1 kN, strain occurs inside the iron-based amorphous alloy strip 2, and the soft magnetic properties deteriorate. Considering the balance between the adhesion strength and the soft magnetic properties, the thermocompression pressure is preferably 100 N or more and 700 N or less per square centimeter, and more preferably 100 N or more and less than 400 N.
[0040] The thickness of the laminate 4 of the iron-based amorphous alloy ribbons 2 formed by the hot pressing step S3 is preferably such that punching can be performed with an efficiency equivalent to that of conventional silicon steel sheets. Specifically, the thickness of the laminate 4 is preferably 80 μm or more and 400 μm or less, more preferably 100 μm or more and 300 μm or less. The thickness of each iron-based amorphous alloy ribbon 2 and the number of laminated sheets can be appropriately set in consideration of the required thickness of the laminate 4.
[0041] <S4: Punching Step> The laminate 4 of the iron-based amorphous alloy ribbons 2 formed by the hot pressing step S3 is conveyed to a punching press 50, and the punching step S4 is performed by the punching press 50. In the punching step S4, the laminate 4 is sandwiched between the upper die and the lower die of the punching press 50 and punched into a predetermined shape, thereby continuously forming punched pieces 5 such as plates for stator cores. A tension roller 51 is provided on the downstream side in the conveying direction of the punching press 50, and the punching process of the laminate 4 can be performed while applying a tension in the direction of arrow A to the laminate 4 by driving the tension roller 51.
[0042] In this way, by conveying the laminate 4 of the iron-based amorphous alloy ribbons 2 obtained by the hot pressing step S3 to the punching press 50 without winding it up and performing the punching step S4, there is no risk of problems such as displacement or peeling of the iron-based amorphous alloy ribbons 2 due to winding of the laminate 4, so that high-quality punched pieces 5 can be efficiently manufactured. After the punched pieces 5 are punched out, the laminate 4 can be wound up, or after being cut to an appropriate length, it can be melted and reused.
[0043] According to the method for manufacturing a laminate of iron-based amorphous alloy ribbons of the present embodiment, a laminate 4 of iron-based amorphous alloys 2 that can be easily punched while ensuring good soft magnetic properties can be obtained.
[0044] Although one embodiment of the present invention has been described above in detail, the specific aspects of the present invention are not limited to the above embodiment. For example, in the pretreatment step S1 of the present embodiment, a heat treatment is performed on a plurality of iron-based amorphous alloy ribbons 1 in a state of being stacked and in close contact with each other, but as shown in Fig. 3, the iron-based amorphous alloy ribbons 1 unwound from each delivery roll 10 may be individually transported to a pretreatment thermostatic bath 20 and heat-treated.
[0045] In this embodiment, the pretreatment step S1, the coating step S2, the thermocompression bonding step S3, and the punching step S4 are performed as a series of steps, but each step may be divided. For example, as shown in Fig. 4(a), the iron-based amorphous alloy ribbon 1 unwound from the delivery roll 10 is transported to a pretreatment thermostatic bath 20 to perform the pretreatment step S1, and the heat-treated iron-based amorphous alloy ribbon 2 is wound up on a first winding roll 11. Next, as shown in Fig. 4(b), a coating step S2 is performed in which adhesive layers 3 are formed on both sides of the iron-based amorphous alloy ribbon 2 unwound from the first winding roll 11 by a coating device 31 and a drying device 32, and then the iron-based amorphous alloy ribbon 2 is wound up on a second winding roll 11. In this way, a plurality of second winding rolls 11 on which the iron-based amorphous alloy ribbon 2 is wound are formed, and then, as shown in Fig. 4(c), the iron-based amorphous alloy ribbon 2 is unwound from the second winding rolls 11, superimposed by bonding rolls 41 and 42, and transported to a thermostatic bath 40 for a thermocompression bonding step S3. The laminate 4 formed in the thermocompression bonding step S3 is then transported to a punching press machine 50 for a punching step S4 to form a punched piece 5. In this way, by appropriately dividing each step S1 to S4, the laminate 4 and the punched piece 5 can be manufactured by effectively utilizing the available space on-site.
[0046] The present invention will be described in more detail below with reference to examples and comparative examples, although the present invention is not limited to the following examples.
[0047] (Example) 200 kg of raw materials containing B, C, Si, P and Fe with a purity of 99.5% or more were inserted into an alumina crucible and melted by high-frequency induction heating to form a molten alloy, so as to obtain the alloy compositions shown in Examples 1-6 in Table 1 below. 50 kg of the molten alloy was poured into an alumina storage vessel having an inner diameter of 200 mm and a height of 400 mm and a BN discharge nozzle with a slit of 0.5 mm wide and 40 mm long at the bottom. A copper alloy quench roll with a diameter of 1000 mm and a width of 200 mm was placed immediately below the discharge nozzle with a gap of 0.4 mm, and the quench roll was rotated at a surface speed of 25 m / s to discharge the molten alloy from the discharge nozzle on the outer peripheral surface, thereby ultra-quenching the molten alloy, and an iron-based amorphous alloy ribbon having an amorphous alloy structure of 90% by volume or more was produced. The thickness of the produced iron-based amorphous alloy ribbon is shown in Table 1. The injection pressure of the molten alloy discharged from the discharge nozzle was 30 kPa, and the amount of cooling water supplied to the inner wall of the chill roll was 300 liters per minute.
[0048] The obtained iron-based amorphous alloy ribbon was subjected to a heat treatment as a pretreatment at a temperature equal to or lower than the crystallization temperature while being continuously transported in the air by a mesh belt furnace. The heat treatment temperature and the heat treatment time at that time are shown in Table 1.
[0049] Next, a plurality of iron-based amorphous alloy ribbons that had been subjected to the heat treatment as a pretreatment were stacked to produce a laminate of iron-based amorphous alloy ribbons. In producing the laminate, a thermosetting resin was uniformly applied to the joining surfaces of the iron-based amorphous alloy ribbons to a thickness of several μm or less, and the ribbons were continuously inserted into a tunnel furnace while being sandwiched between pressure rolls, and subjected to a thermocompression treatment in the atmosphere. The number of layers, thermocompression temperature, thermocompression time, thermocompression force, and thickness of the obtained laminate are shown in Table 2.
[0050] After evaluating the soft magnetic properties (saturation magnetic flux density Bs, relative magnetic permeability μr, and iron loss) of the obtained laminate, a punching test was performed using a punching press, and the adhesion of each iron-based amorphous alloy ribbon after punching was evaluated by classifying the adhesion into three categories: ◯ when no peeling between the ribbons was observed, △ when partial peeling was observed, and × when complete peeling was observed. The evaluation results are shown in Table 3 below.
[0051] (Comparative Example) Molten alloys were prepared so as to have the alloy compositions shown in Comparative Examples 7-11 in Table 1 below, and iron-based amorphous alloy ribbons were produced from the molten alloys. The production conditions for Comparative Examples 7-10 were the same as those for Examples 1-6, except that the size of the slit in the discharge nozzle was 0.3 mm wide and 40 mm long. Meanwhile, the production conditions for Comparative Example 11 were the same as those for Examples 1-6, including the size of the slit in the discharge nozzle.
[0052] Thereafter, the iron-based amorphous alloy ribbons of Comparative Examples 7, 10, and 11 were subjected to a heat treatment as a pretreatment in a mesh belt furnace in the same manner as in Examples 1-6. The heat treatment temperature and the heat treatment time are shown in Table 1. The heat treatment temperature in Comparative Example 11 is a temperature higher than the crystallization temperature of the iron-based amorphous alloy ribbon having an amorphous structure. On the other hand, the iron-based amorphous alloy ribbons of Comparative Examples 8 and 9 were not subjected to a heat treatment as a pretreatment.
[0053] Next, similarly to Examples 1-6, laminates of iron-based amorphous alloy ribbons were produced under the conditions shown in Table 2, and the soft magnetic properties (saturation magnetic flux density Bs, relative magnetic permeability μr, and iron loss) of the obtained laminates were evaluated, and then a punching test was carried out using a punching press to evaluate the adhesion of each iron-based amorphous alloy ribbon after punching. The evaluation results are shown in Table 3 below.
[0054] [Table 1]
[0055] [Table 2]
[0056] [Table 3] [Explanation of symbols]
[0057] 1 Iron-based amorphous alloy ribbon 2. Iron-based amorphous alloy ribbon after heat treatment 3 Adhesive layer 4. Laminate 5 punching pieces 10 Sending Roll 20 Pretreatment thermostatic chamber 21,22 Pressure roll 31 Coating equipment 32 Drying equipment 40 Temperature bath for thermocompression 41,42 Pressure roll 50 Punching press machine S1 Pretreatment process S2 coating process S3 Heat compression bonding process S4 Punching process
Claims
1. A method for manufacturing a laminate by laminating a plurality of iron-based amorphous alloy ribbons, comprising the steps of: The iron-based amorphous alloy ribbon has a composition formula T 100-x-y-z S x (B 1-m C m ) y P z (T is at least one element selected from the group consisting of Fe, Co, and Ni, and is a transition metal element that necessarily includes Fe), and has a composition in which the composition ratios x, y, z, and m satisfy 2.5≦x≦7.0 atomic %, 13.0≦y≦16.0 atomic %, 0.0≦z≦2.0 atomic %, and 0.0≦m≦0.3, respectively, and has a thickness of 30 μm or more and 60 μm or less, a pretreatment step of heat-treating a plurality of the iron-based amorphous alloy ribbons at a temperature of 200° C. or higher and lower than a crystallization temperature; a coating step of coating at least one of the plurality of iron-based amorphous alloy ribbons after the heat treatment with a thermosetting resin to form an adhesive layer; and a thermocompression bonding step of thermocompression bonding a plurality of the iron-based amorphous alloy ribbons via the adhesive layer to form a laminate.
2. 2. The method for producing a laminate of iron-based amorphous alloy ribbons according to claim 1, wherein the pretreatment step comprises heat treatment for a heat treatment time of 0.01 seconds to 2 hours.
3. The pretreatment step includes: stacking a plurality of the iron-based amorphous alloy ribbons in close contact with each other and subjecting them to a heat treatment; 2. The method for producing a laminate of iron-based amorphous alloy ribbons according to claim 1, wherein the coating step separates the overlapped iron-based amorphous alloy ribbons to form the adhesive layer.
4. 2. The method for producing a laminate of iron-based amorphous alloy ribbons according to claim 1, further comprising a punching step of conveying the laminate of the iron-based amorphous alloy ribbons obtained by the thermocompression bonding step to a punching press without winding it up, and punching the laminate into a predetermined shape by the punching press to form a punched piece.
5. 2. The method for producing a laminate of iron-based amorphous alloy ribbons according to claim 1, wherein the thermocompression bonding step is performed by holding the laminate at a temperature of 120° C. or more and less than 400° C. for 1 second or more and less than 2 hours, and the thickness of the laminate of the iron-based amorphous alloy ribbons is 80 μm or more and 400 μm or less.
6. 2. The method for producing a laminate of iron-based amorphous alloy ribbons according to claim 1, wherein a pressure in the thermocompression step is 30 N or more and 1 kN or less per square centimeter.
7. 2. The method for producing a laminate of iron-based amorphous alloy ribbons according to claim 1, wherein the iron-based amorphous alloy ribbons that have been subjected to the pretreatment process have a Bs of 1.4 T or more, a magnetic permeability of 3000 or more, and an iron loss of 30 W / kg or less at Bm = 1.0 T and a frequency of 1 kHz.
Citation Information
Patent Citations
Heat treatment method for amorphous magnetic alloy sheet
JP1979083622A
Manufacture of electromagnetic steel plate
JP1982039510A
Production of metal strip and nozzle for production
JP1988220950A
Production of thin strip of amorphous alloy having large thickness
JP1993329587A
Ferrous amorphous alloy
JP1995113151A